The governance of Islamic extremism in the Middle East: a multidimensional assessment and implications - Zhiqiang Zou; Li Li (Asian Review of Political Economy)
Abstract Given the significant religious connotations, political demands, and social implications associated with Islamic extremism, it is crucial that counter-extremism strategies address a wide array of areas. This is particularly vital in the realms of political participation, religious management, and social governance, all of which are essential for the prevention of Islamic extremism. The complexity and diversity present in the political, religious, and social landscapes of Middle Eastern countries have led to variations in the policies and effectiveness of governance approaches related to Islamic extremism. These variations provide valuable lessons and insights. This article aims to analyze the differences and implications of governance approaches to extremism in the Middle East through a multidimensional assessment of the interrelations among politics and religion, religious-secular relations, and state-society relations. Rather than categorizing these approaches as inherently positive or negative, it is imperative for each country to identify governance strategies that are congruent with its unique circumstances.